Regulations for the Admission of Out-Patients
1902-01-04 1902 1900s 3 pages Great Northern Central Hospital. REGULATIONS FOR THE ADMISSION OF OUT-PATIENTS. As approved by the Committee of Management January 3rd, 1896. 1. The Hospital is intended for the relief of the Sick Poor only 2. First aid is rendered in all cases applying to the Hospital for relief. 3. A form of certificate is given to all patients who fail to satisfy the Inquiry Officer as to their fitness for gratuitous treatment, and it must be presented duly signed before the patient is treated a second time. 4. The fitness or unfitness of any patient for gratuitous relief is, as far as possible, determined upon a wages scale, with certain clearly defined exceptions. 5. The following require a certificate in accordance with Regulation 3:— (а) Unmarried men and women, in work, who pay all their own expenses of board and lodging, and are earning more than 25 shillings and 20 shillings a week respectively. (b) Unmarried men, in work, living with their parents or employers, and earning more than 15 shillings a week. Unmarried women, under similar conditions, earning more than 12 shillings a week. (c) Married men, in work, earning more than 30 shillings a week, if without a family ; and the wives of such men. (d) Married men, with from one to three children, under six years of age, earning more than 40 shillings a week. (e) Married men with more than three children, earning more than 35 shillings a week, where some of the children are able to work. (f) Wives and children in the last two classes, where the husband or father is in work. 6. No member of a family, the united earnings of which amount to 30 shillings or more, is admissible, except under special circumstances and after due inquiry. 7. Patients coming to the out-patient department are in all cases questioned as to the amount of wages earned by themselves or by the bread-winner of their families. 8. If the wages or income from all sources amount to more than the wage limit in each class, an inquiry sheet is filled up with the particulars of the case and a form of certificate issued, which must be returned, duly signed, at the next visit. 9. Besides the amount of wages Patients must state whether there are other sources of income, such as earnings of wife or children, grants from clubs, rents from letting lodgings, or gratuities, as in the case of railway servants. They must also give the following details:— The number of dependents upon the bread winner, other than wife and children, the want of work, whether from illness or other cause, the duration of the illness under which the patient is suffering, the name of hospital, dispensary, or private doctor under whom the patient may have been treated, the names of clubs and club doctors, whether the patient is a member of a provident dispensary; and rent of the dwelling-house or lodging. 378/IMSW/A/1/6/9a